Investigation on the Secondary Generation of Natural Gas Hydrates in Horizontal Wellbore Caused by Pressure Jump during the Depressurization Development of Hydrate Bearing Layers - Qingjun Du; Yongge Liu; Jian Hou; Lina Shi; Wenbin Wang; Kang Zhou (Geofluids)
When the depressurization development of a hydrate-bearing layer is initiated, the temperature of the near-wellbore formation quickly decreases to near the equilibrium temperature due to the dissociation of natural gas hydrate Therefore, the secondary generation of natural gas hydrates in the wellbore easily occurs if pressure jumps to a high value due to the changes of production rates or shutdown of the well. Though hydrate generation in the process of high-pressure drilling and gas and water transportation has been widely investigated, the secondary generation of natural gas hydrates caused by pressure jump during the depressurization development process is not fully understood. In this study, the multiphase pipe flow of a horizontal well, the Vyniauskas–Bishnoi generation dynamics of natural gas hydrate, and a decomposition dynamics model developed by Kim and Bishnoi are combined to build a set of horizontal well gas–liquid–solid three-phase flow models, which consider the phase transition in the wellbore and distinguished the secondary hydrate generation area in the wellbore under different temperature and pressure conditions. The results show that when the toe-end pressure is 7 MPa and the environment temperature is 6.4°C, the secondary hydrate generation exists in the horizontal section of the horizontal well, and the maximum hydrate flow velocity in the wellbore is 0.044 m3/d. A high toe-end pressure, low environment temperature, and high gas output will result in a greater hydrate generation in the wellbore, and the wellbore pressure will have a remarkable influence on the amount generated and its range.